Mieres Reborn : The Reinvention of a Catalan Community - Robertson, A. F. (Book collections on Project MUSE., 2012)
Mieres Reborn reveals how patient observation and an analysis of one small community have much to tell us about human progress more generally. Not long ago Mieres, a village in the eastern foothills of the Pyrenees, seemed destined to die. As in countless thousands of rural communities around the world, young people in Mieres over the years have moved to the towns and cities, leaving behind abandoned fields and meadows, derelict houses, and their aging and disconsolate parents and grandparents. Close observation of this social microcosm over two decades reveals the capacity of ordinary.